Molecular mechanisms underlying age-dependent effects of rearing system on the goose testicular development and semen quality - Shenqiang Hu; Xiaopeng Li; Enhua Qing; Junqi Wang; Qingliang Chen; Yang Song; Jiasen Chen; Jiwei Hu; Liang Li; Jiwen Wang (Poultry Science)
As an important non-genetic factor, the rearing system has significant effects on male poultry reproductive system development. However, compared with other poultry such as chickens and ducks, less is known about the effects and mechanisms of rearing system on the gander reproductive organ development and semen quality. In the present study, the testicular morphological, histological, and transcriptomic responses of three goose breeds to the two dryland rearing systems (i.e., cage rearing system, CRS and net-floor mixed rearing system, MRS) were systematically analyzed and compared. Results from histomorphological analysis demonstrated that the effects of rearing system on the gander testicular development were age-dependent, and moreover, the CRS may be more conducive than MRS to the testicular development and semen quality during the period from post-hatch week 10 to week 43. At week 30, compared to Sichuan White goose (SW), the rearing system showed more pronounced effects on the testicular size, weight, and organ index of Gang goose (GE) and Landes goose (LD). However, such effects were mitigated in LD and even reversed in GE at week 43. Meanwhile, most testicular histological parameters of three goose breeds were higher under MRS than under CRS at week 30, while the converse was seen in some histological parameters of either GE or LD at week 43. Moreover, the semen quality was generally better under CRS than under MRS at week 43. Through comparative transcriptomics analysis, the Wnt signaling pathway together with several involved hub genes were identified to have important roles in mediating the effects of rearing system on the goose testicular development. Moreover, the metabolism-related, cell cycle, and Wnt signaling pathways could be partially responsible for differences in the goose breed-related testicular development and semen quality under CRS, where a number of genes involved in meiosis could have crucial roles. These results would not only provide novel insights into the effects and mechanisms of rearing system on male poultry reproductive performance, but they would also be helpful for the optimization and selection of dryland rearing systems in male geese.